The half-life of Molly Pierce - Leno, Katrina (HarperTeen, 2014)
"Molly, a seventeen-year-old girl who suffers from dissociative identity disorder, has played host to Mabel, a completely distinct personality, for most her life. When Molly faces a crisis Mabel doesn't know she can handle, Mabel lets Molly in on her secrets"..
Keywords: Multiple personality; Dissociative disorders; Psychische Belastung; Identitätsfindung; Weibliche Jugend; Gedächtnisstörung; Wahrheit; Jugendbuch